Environmental Attitudes and Knowledge: Do They Matter for Support and Investment in Local Stormwater Infrastructure?. Issue 7 (3rd July 2021) - Pierce, Gregory; Gmoser-Daskalakis, Kyra; Rippy, Megan A.; Holden, Patricia A.; Grant, Stanley B.; Feldman, David L.; Ambrose, Richard F.
Abstract: Stormwater infrastructure substantially impacts water quality and supply. In the U.S., local agency investments rely on public support from taxes or fees. Assessing individuals' knowledge and willingness to pay helps inform potential pathways to funding and green infrastructure implementation. Using a 2018–2019 survey of 868 University of California students and staff, we analyze stormwater knowledge and willingness to pay or support public fund allocation for green infrastructure, especially natural treatment systems (NTS). Results of three separate regression models, each with a one-campus random sample and an all-campus convenience sample, show the majority of respondents supported allocating personal and campus funds for NTS. Preexisting environmental attitudes (on the New Ecological Paradigm scale) were the most common driver in nearly all models, but with inconsistent results and low explanatory power across models. Harnessing public support to increase stormwater investment may require tailored benefit messaging or other motivational frameworks, particularly in semiarid environments.